Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Tìm số nguyên x, biết:
1) -16 + 23 + x = - 16
7+x=-16
x=-16-7
x=-23
2) 2x – 35 = 15
2x=15+35
2x=50
x=50:2
x=25
3) 3x + 17 = 12
3x=12-17
3x=-5
x=-5/3
4) (2x – 5) + 17 = 6
2x-5=6-17
2x-5=-11
2x=-11+5
2x=-6
x=-6:2
x=-3
5) 10 – 2(4 – 3x) = -4
2(4-3x)=10-(-4)
2(4-3x)=14
4-3x=14:2
4-3x=7
3x=4-7
3x=-3
x=-3:3
x=-1
6) - 12 + 3(-x + 7) = -18
3(-x+7)=-18-(-12)
3(x+7)=-6
x+7=-6:3
x+7=-2
x=-2-7
x=-9
Sửa đề: \(2x+\dfrac{11}{6}+\dfrac{23}{12}+\dfrac{39}{20}+\dfrac{59}{30}+\dfrac{83}{42}+\dfrac{111}{56}=12\)
\(\Leftrightarrow2x+\left(2+2+2+2+2+2\right)-\left(\dfrac{1}{6}+\dfrac{1}{12}+\dfrac{1}{20}+\dfrac{1}{30}+\dfrac{1}{42}+\dfrac{1}{56}\right)=12\)
\(\Leftrightarrow2x-\left(\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{1}{3}-\dfrac{1}{4}+...+\dfrac{1}{7}-\dfrac{1}{8}\right)=0\)
\(\Leftrightarrow2x-\dfrac{3}{8}=0\)
hay x=3/16
\(1,2x+3x-4x=\left(-2\right)^3\)
<=>\(x=-8\)
\(2,x-2x=4^2+4^0\)
<=>\(-x=16+1\)
<=>\(-x=17\)
<=>\(x=-17\)
\(3,2^3x-3^2x=|12-21|\)
<=>\(-x=9\)
<=>\(x=-9\)
\(4,x-45=2x+54\)
<=>\(x-2x=54+45\)
<=>\(-x=99\)
<=>\(x=-99\)
\(5,5x-12+23=6^7:6^5\)
<=>\(5x+11=6^2\)
<=>\(5x+11=36\)
<=>\(5x=25\)
<=>\(x=5\)
Bài 2:
a) \(\left(3x+2\right)^3=-64\)
\(\Leftrightarrow\left(3x+2\right)^3=\left(-4\right)^3\)
\(\Leftrightarrow3x+2=\left(-4\right)\)
\(\Leftrightarrow3x=-4-2\)
\(\Leftrightarrow3x=-6\)
\(\Leftrightarrow x=-2\)
b) \(2x-3=-33\)
\(\Leftrightarrow2x=-33+3\)
\(\Leftrightarrow2x=-30\)
\(\Leftrightarrow x=-15\)
2x+20=-22
=> 2x = -22 - 20
=> 2x = -42
=> x = -42 : 2
=> x = -21
Vậy x = -21
2x+20=-22
2x=-22-20
2x=-42
x=-42:2
x=-21
-(-30)-(-x)=13
30+x=13
x=13-30
x=-17
-(-x)+14=12
x+14=12
x=12-14
x=-2
x+20=-(-23)
x+20=23
x=23-20
x=3
15-x+17=-(-6)+|-12|
15+17+x=6+12
32+x=18
x=18-32
x=-14
-|-5|-(-x)+4=3-(-25)
-5+x+4=3+25
-5+4+x=28
-1x=28
x=28:(-1)
x=-28
2,a, \(12⋮2x+1\)
\(\Rightarrow2x+1\inƯ\left(12\right)=\left\{\pm1;\pm2;\pm3;\pm4;\pm6;\pm12\right\}\)
2x + 1 | 1 | -1 | 2 | -2 | 3 | -3 | 4 | -4 | 6 | -6 | 12 | -12 |
2x | 0 | -2 | 1 | -3 | 2 | -4 | 3 | -5 | 5 | -7 | 11 | -13 |
x | 0 | -1 | 1/2 | -3/2 | 1 | -2 | 3/2 | -5/2 | 5/2 | -7/2 | 11/2 | -13/2 |
Vì \(x\in N\)=> x = 0 ; 1
b, \(2x+6⋮2x-1\)
\(2x-1+7⋮2x-1\)
Vì \(2x-1⋮2x-1\)
\(7⋮2x-1\)=> \(2x-1\inƯ\left(7\right)=\left\{\pm1;\pm7\right\}\)
2x - 1 | 1 | -1 | 7 | -7 |
2x | 2 | 0 | 8 | -6 |
x | 1 | 0 | 4 | -3 |
Vì \(x\in N\)=> x = 1; 0 ; 4
`12-(2X+23)+12:2=6`
`12-(2X+23)+6=6`
`6+(2x+23) =6`
`2x+23 = 6-6=0`
`2x=23`
`x=23/2`
12 - (2x + 23) + 12: 2 = 6
12 - (2x + 23 ) + 6 = 6
12 -(2x+23) = 6 - 6
12 - (2x + 23) =0
2x + 23 = 12
2x = 12 - 23
2x = -11
x = -11 : 2
x = -11/2